2011
DOI: 10.1007/s00122-011-1535-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci analysis for resistance to Cephalosporium stripe, a vascular wilt disease of wheat

Abstract: Cephalosporium stripe, caused by Cephalosporium gramineum, can cause severe loss of wheat (Triticum aestivum L.) yield and grain quality and can be an important factor limiting adoption of conservation tillage practices. Selecting for resistance to Cephalosporium stripe is problematic; however, as optimum conditions for disease do not occur annually under natural conditions, inoculum levels can be spatially heterogeneous, and little is known about the inheritance of resistance. A population of 268 recombinant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 81 publications
5
31
0
Order By: Relevance
“…Another class of defense-associated proteins is composed of serine/threonine protein kinase (S/TPK) domain (Faris et al 2010;Lorang et al 2007). They reported a QTL in chromosome 5AL that is located in the same region as 5AL.1 for Cephalosporium stripe found in E/T, T/N populations and in C/B (Quincke et al 2011). Lillemo et al (2013) reported a QTL for the necrotrophic pathogen spot blotch (Bipolaris sorokiniana, telemorph Cochliobolus sativus) that co-locates to the locus Lr34, which provides resistance to leaf rust (Puccinia triticina Eriks).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Another class of defense-associated proteins is composed of serine/threonine protein kinase (S/TPK) domain (Faris et al 2010;Lorang et al 2007). They reported a QTL in chromosome 5AL that is located in the same region as 5AL.1 for Cephalosporium stripe found in E/T, T/N populations and in C/B (Quincke et al 2011). Lillemo et al (2013) reported a QTL for the necrotrophic pathogen spot blotch (Bipolaris sorokiniana, telemorph Cochliobolus sativus) that co-locates to the locus Lr34, which provides resistance to leaf rust (Puccinia triticina Eriks).…”
Section: Discussionmentioning
confidence: 80%
“…This region was identified previously (Quincke et al 2011), located close and probably pseudo-linked to the B1 gene conditioning the awnless trait (Kato et al 1998). The QTL 5AL.1 linked to marker gwm291 was detected consistently across environments in both populations, making it a good candidate for use in marker-assisted selection.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The Brundage by Coda population has previously been genotyped using SSR (simple sequence repeat; Xbarc , Xpsp , Xwmc , Xgwm , Xgdm ) and DArT (Diversity Array Technology; wPt ) genetic markers as described in Quincke et al [22], Johnson et al [23] and Leonard et al [21]. Single nucleotide polymorphism (SNP) markers ( Xiwa ) were evaluated on the population using the Illumina GoldenGate assay as described by Akhunov et al [31] and Cavanagh et al [32].…”
Section: Methodsmentioning
confidence: 99%
“…The soft white winter wheat ( T. aestivum L.) mapping population created from the cross ‘Brundage’ (PI 599193) by ‘Coda’ (PI 594372) at the University of Idaho has been used to map several traits including Pch1 resistance to eyespot caused by Oculimacula yallundae [21], Cephalosporium stripe caused by Cephalosporium gramineum [22], and the compactum locus [23]. The population also segregates for resistance to stripe rust.…”
Section: Introductionmentioning
confidence: 99%